Assessment of Green areas criteria regarding women-friendly city concept: case study of çiğli - Mercan Efe Güney; Filiz Ay; Beste Tuncay; Sıdal Tanrıverdi; Nurseli Şanli; Hacer Akbudak (Cogent Social Sciences, 2022)
Turkish women use cities as service areas where they practice their social gender roles. Parks are one of these service areas. This study aims to propose ways to analyze and assess green areas as public places regarding the women-friendly city concept as a way of promoting gender equality. The study claims that planning and constructing a green area is insufficient to create a public place, and the existence of a green area does not mean that it can be used. Furthermore, green areas should be approached in a context where their existence is not merely limited to their square meter ratios per person. Thus, green areas should be planned with a women-friendly perspective which meets the needs and demands of all users and with an approach that overcomes the intersectionality-blindness of planning.This study analyzes green areas based on the following three categories: accessibility, safety, and usability. The findings revealed that no parks met these criteria, especially in the densely used areas. Furthermore, problems related to all the three criteria were observed in the central area, and as people moved away from this area, issues related to accessibility and security came to the fore.